Distribution of the Recombinant Coagulation Factor 125I-rFVIIa in Rats - Beeby, T L; Chasseaud, L F; Taylor, T; Thomsen, M K (Thrombosis and Haemostasis, 1993)
Recombinant human factor VIIa (rFVIIa; NovoSeven®) is a two-chain activated clotting factor that is used in the treatment of haemophilia. The distribution of radioactivity in male and pregnant and non-pregnant female rats has been examined by whole-body autoradiography (WBA) after single intravenous doses of 125I-radiolabelled rFVIIa at a dosage level of ca. 0.1 mg/kg.Concentrations of radioactivity were highest in the blood and the highly perfused major thoracic and visceral organs and gonads. This distribution of radioactivity was generally similar in pregnant and non-pregnant females, and although radioactivity was concentrated in the foetal thyroid, it was present in other foetal tissues only at trace levels. Radioactivity in thyroid, urinary bladder and gastrointestinal tract of all rats was apparently associated with detached 125I-iodide. At early sacrifice times (up to 2 h), radioactivity was present in the bone marrow, but at later times (6-24 h) it was apparently associated with the mineralised bone structures.The quantitative distribution of total and trichloroacetic acid precipitable radioactivity in the tissues of rats also was studied after single intravenous doses of 125I-rFVIIa and 125I-rFVII, the non-activated single chain precursor of FVIIa, which is normally present in the circulation. These studies confirmed the WBA findings and showed that the tissue distribution of 125I-rFVII and 125I-rFVIIa was similar, indicating that the distribution of rFVIIa during therapy would be similar to that produced from endogenous FVII as a physiological response to vascular injury.